Resident Operative Vaginal Delivery Volume after Educational Curriculum Implementation - Becker, David A.; Blanchard, Christina T.; Szychowski, Jeff M.; Rogers, Sharee L.; Brumfield, Cynthia G.; Subramaniam, Akila (American Journal of Perinatology, 2020)
Objective The percentage of operative vaginal deliveries (OVDs) in the United States has sharply declined. In May 2016, our institution's obstetrics and gynecology (OB/GYN) residency program implemented a twice-yearly OVD curriculum consisting of didactics and simulation. We sought to evaluate the impact of this curriculum.Study Design We performed a retrospective cohort study of all deliveries at our institution from July 2011 to May 2018. Deliveries were evaluated quarterly for the pre- (July 2011–April 2016) and postcurriculum (July 2016–May 2018) periods. Forceps-assisted vaginal delivery (FAVD), vacuum-assisted vaginal delivery (VAVD), and total OVD percentages, and the ratio of forceps to vacuums were calculated. Pre- and postcurriculum percentages were compared using Wilcoxon's rank-sum test. Cubic regression curves were fit to quarterly percentages to illustrate trends over time.Results The quarterly OVD percentage was unchanged following curriculum implementation (mean 3.2% [Q1–Q3: 2.6–3.5%] pre- vs. 3.1% [2.5–3.8%] post-, p > 0.99). The FAVD percentage was increased (1.2% [0.8–1.5%] vs. 2.0% [1.4–2.6%], p = 0.027) and the VAVD percentage was decreased (2.0% [1.6–2.2%] vs. 1.2% [0.9–1.3%], p < 0.001). This was accompanied by an increase in the ratio of FAVD to VAVD (0.6 [0.4–0.8] vs. 1.7 [1.3–2.2], p < 0.001). FAVD percentage (3.1%) was higher in the last quarter than any other quarter in the 7-year study period, and total OVD percentage (3.9%) was higher in 2018 than any other calendar year.Conclusion The implementation of an OVD curriculum in our OB/GYN residency program resulted in an increase in the percentage of FAVD and the ratio of FAVD to VAVD.Key Points
Keywords: forceps; operative vaginal delivery; resident education; vacuum